2004
DOI: 10.1080/02640410310001655804
|View full text |Cite
|
Sign up to set email alerts
|

Groin injuries in professional rugby league players: a prospective study

Abstract: Altogether, 100 uninjured professional rugby league players were evaluated over a 2-year period. Their height, body mass, sum of skinfolds, girths and bone diameters were recorded. A Cybex 340 isokinetic dynamometer was used to determine peak torque, work, power, endurance ratios and peak torque ratios of the hip abductors and adductors (5 repetitions at 0.52 and 2.08 rad. s(- 1); 20 repetitions at 3.66 rad. s(- 1)) and knee flexors and extensors (4 repetitions at 1.04 and 3.14 rad. s(- 1); 30 repetitions at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 23 publications
2
75
0
1
Order By: Relevance
“…When analysed further they concluded that if the adduction strength was 80 % or less than that of the abductor strength then you were 17 times more likely to get a groin strain. This philosophy of hip muscle ratio balance being important versus peak strength has been echoed by O'Connor [ 15 ] who commented on an over focus on gluteals at the expense of the adductors, allows the ratio to become poor. He goes on to mention that the Hip fl exors should be incorporated into this and that the focus should be on total hip strength.…”
Section: Adductor Muscle Injuriesmentioning
confidence: 96%
See 2 more Smart Citations
“…When analysed further they concluded that if the adduction strength was 80 % or less than that of the abductor strength then you were 17 times more likely to get a groin strain. This philosophy of hip muscle ratio balance being important versus peak strength has been echoed by O'Connor [ 15 ] who commented on an over focus on gluteals at the expense of the adductors, allows the ratio to become poor. He goes on to mention that the Hip fl exors should be incorporated into this and that the focus should be on total hip strength.…”
Section: Adductor Muscle Injuriesmentioning
confidence: 96%
“…O'Connor [ 15 ] reported that 23 % of all injuries over two seasons (n = 100) in rugby union occurred in the adductor muscles. While Molsa et al [ 16 ] commented that in ice hockey adductor muscle injuries accounted for 43 % of all muscle strains over three seasons (n = 134).…”
Section: Adductor Related Groin Pain Adductor Muscle Strainmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerous authors have reported predisposing factors to groin and hip pathologies, most notably reduced total hip range of motion (ROM) (Malliaras, Hogan, Nawrocki, Crossley, & Schache, 2009;Tyler, Nicholas, Campbell, & McHugh, 2001;Verrall, Hamilton, et al, 2005;Verrall, Slavotinek, Barnes, et al, 2007;Williams, 1978) and hip strength profiles, particularly into abduction and adduction (Delahunt, McEntee, Kennedy, Green, & Coughlan, 2011;Emery & Meeuwisse, 2001;Malliaras et al, 2009;O'Connor, 2004;Thorborg et al, 2011;Tyler et al, 2001). Other factors mentioned include reduced trunk control seen in chronic 'groin pathologies (Bradshaw & Holmich, 2009;Cowan et al, 2004;McCarthy & Vicenzino, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…Active rehabilitation involved the athlete commencing gentle transversus abdominus (TrA) (Cowan et al, 2004), internal and external oblique (IO/EO) activation, abductor strengthening (Malliaras et al, 2009;O'Connor, 2004;Thorborg et al, 2011;Tyler et al, 2001) and light cross-training via a stationary bike to maintain cardiovascular fitness.…”
Section: Acute Pharmacological Managementmentioning
confidence: 99%